Library Professionals' and partners' implicit principle of non-interference and writing-related interventions - Kämäräinen, Juha; Saarti, Jarmo (Qualitative and Quantitative Methods in Libraries; Vol 3 No 4 (2014): December 2014 Issue, 2017)
The utilization of the full potential of the staff of the Finnish Universities of Applied Sciences (UAS) is hindered by organizational barriers and prejudices about what represents the suitable contribution from the information searching and management professionals. Barriers related to the division of labor between teachers and library professionals in shared writing-related tasks are discussed in this article and an interventionist approach is suggested. A significant barrier disabling the information specialist's work is defined here as the principle of non-interference. The concept is sketched as a discourse that limits the contribution of the library mainly to the metainformation management. The limitation is further analyzed in terms of the activity system model from the theory of action and the actantial model from the generative trajectory approach. Changes in the positions of information specialists and library values towards the partnership in the research and development is suggested in order to overcome the limitations caused by the principle.